Decreased expression of SCARA5 predicts a poor prognosis in melanoma using bioinformatics analysis - Ni, Qinggan; Li, Xia; Huang, Hua; Ge, Zili (Frontiers in Oncology, 2023)
Background: It has been established that the scavenger receptor class A member 5 (SCARA5) functions as a tumor suppressor gene in various cancer types. To our knowledge, no comprehensive study has hitherto investigated the expression and function of SCARA5 in melanoma. This study aimed to determine the association between SCARA5 and melanoma. Methods: Analysis of SCARA5 mRNA expression was performed using The Cancer Genome Atlas (TCGA) datasets. To evaluate the clinical significance of SCARA5, the clinical data for 93 patients with melanoma were collected. The role of SCARA5 expression in prognosis was also analyzed. In this study, survival was evaluated by Kaplan-Meier analysis and compared using the log-rank test. Univariate and multivariate Cox proportional hazard regression analyses were used to identify independent predictors. Kyoto Encyclopedia of Genes and Genomes/Gene Ontology and Gene Set Enrichment Analysis (GSEA) were used to perform gene set functional annotations. PPI networks were constructed to illustrate gene-gene interactions. The Tumor IMmune Estimation Resource (TIMER) database was used to explore the association between SCARA5 and immune infiltration levels. Results: The results showed that the SCARA5 mRNA expression in melanoma was significantly lower than in adjacent normal skin tissue (p<0.001). Moreover, decreased expression of SCARA5 in melanoma correlated with the TMN stage and recurrence (p<0.05). The overall survival (OS) was significantly higher in melanoma with high SCARA5 expression compared with low SCARA5 expression (P<0.001). During univariate analysis, SCARA5 expression, T stage, N stage, M stage, and recurrence correlated with OS (p < 0.05). Further multivariate Cox regression analysis showed that SCARA5 expression (p=0.012) could be an independent prognostic factor for OS in cutaneous malignant melanoma. GSEA analysis showed SCARA5 was significantly enriched in various pathways, such as response to developmental biology and response to antimicrobial peptides. Correlation analysis showed a positive correlation with CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells (P<0.05) and a negative correlation with tumor purity (P<0.05) Conclusion: SCARA5 has huge prospects as a prognostic biomarker and promising therapeutic target in melanoma. Furthermore, SCARA5 expression in melanoma is related to the level of immune infiltration.